2015
DOI: 10.1364/ao.54.006491
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of statistical properties of a randomly fluctuating polarized field

Abstract: An experimental technique for the synthesis of statistical properties of a randomly fluctuating polarized field is investigated and experimentally demonstrated. The technique offers the controlled synthesis of coherence and polarization and subsequent analysis of the synthesized field is carried out by making use of two-point intensity correlation and the speckle holographic technique. The controlled synthesis is achieved by using an aperture of specific size at the source plane and generating a vortex in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In another work, it is theoretically predicted that the interference of two unpolarized fields can produce completely polarized and depolarized field depending on the spatial position [32]. It is also shown that the correlation of the polarization elements can be manipulated using a spiral phase plate (SPP) and by different holographic techniques [33][34][35]. In another recent development, generation of partially coherent beams with different complex degrees of coherence is demonstrated experimentally [36].…”
mentioning
confidence: 99%
“…In another work, it is theoretically predicted that the interference of two unpolarized fields can produce completely polarized and depolarized field depending on the spatial position [32]. It is also shown that the correlation of the polarization elements can be manipulated using a spiral phase plate (SPP) and by different holographic techniques [33][34][35]. In another recent development, generation of partially coherent beams with different complex degrees of coherence is demonstrated experimentally [36].…”
mentioning
confidence: 99%
“…The GDH system exploits the wide-sense spatial stationarity of the scattered fields at the detector plane and implements the spatial averaging approach as a replacement of ensemble averaging in the execution of correlation of intensity fluctuations. In recent times, a significant number of research efforts in correlation-based imaging and characterization techniques utilizes the potential features of spatial statistical optics [41,43,[69][70][71][72][73][74], but the approach has only very few executions in ghost scenarios [29]. The utilization of spatial averaging provides the potential opportunity to develop the snapshot GDH system, where the single shot detection of two intensity distributions corresponding to the ghost diffraction fields are sufficient to retrieve the ghost correlation hologram, thereby the simultaneous quantitative phase and amplitude imaging.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Coherence singularities in propagating coherent and partially coherent optical fields have been studied [36][37][38][39]. In the recent past, technique for the controlled synthesis of coherence and polarization were investigated by making use of intensity correlations [40]. Also, first-order polarization correlation singularity and stokes field auto-correlation (fourth-order correlation) singularities were studied in the vector speckle far-field generated from the scattering of Poincare beam [41][42][43].…”
Section: Introductionmentioning
confidence: 99%